Interest‐Talk as Access‐Talk: How Interests are Displayed, Made and Down‐played in Management Research2. (10th May 2013) - Whittle, Andrea; Mueller, Frank; Lenney, Peter; Gilchrist, Alan
<x xml:space="preserve">Abstract</x> This paper addresses the methodological issue of how researchers gain access and build trust in order to conduct research in organizations. It focuses, in particular, on the role of interests (what actors want or what they stand to gain or lose) in the research relationship. The analysis shows how notions of interests, stake and motive were managed during an action research study in a UK subsidiary of a multinational corporation. The study uses an approach to discourse analysis inspired by the field of discursive psychology to identify four discursive devices: stake inoculation; stake confession; stake attribution; and stake construction. The paper contributes to the understanding of research methodology by identifying the importance of interest‐talk in the process of doing management research.